Campaña de lanzamiento para la nueva marca de energizantes: Boom Power - Armas Pietersz, Ximena Belén (2023)
This project consists of the creation of the launch campaign for "Boom Power", a new brand of energy drinks that will arrive in Peru in August and seeks to revolutionize the market by offering local quality ingredients in its formula at a more accessible price. This plan aims to achieve awareness and recall in our target and achieve a 12% market share at the end of the first year of the launch. In order to achieve this, an exhaustive research of the target audience was carried out to understand the behavior of the target in relation to this beverage. In this way, we determined that people who consume it are mostly looking for a product that gives them a boost of energy in situations in which they feel very tired. For this reason, we created "Boom Power", a drink whose purpose is to provide energy in a natural way at a better price. From this we developed a media strategy that will help us meet our objectives and will be measured through KPI's to determine its effectiveness.